Awareness of the costs of selected medical procedures and the use of healthcare among young adults in Poland - Anna Rogalska; Karolina Sobczyk; Tomasz Holecki (Kazimierz Wielki University, 2022)
Aim:  The study aimed to test students' awareness of the costs of selected medical procedures. Another aim was to identify the frequency of used medical benefits both as part of public and private medical care. Materials and Methods: The research group included 246 people, both women, and men, aged 19-29, studying in Poland. An anonymous research questionnaire was used to conduct the study, which was sent to 21 universities in Poland (medical universities and physical education academies). The questionnaire asked participants to estimate the costs of treatments and investigations. The respondents were also asked which services of medical specialists they used in the last year. Results: Outpatient specialist care services under the public health care system were used by the majority of respondents (N = 200; 81.3%). Most often it was 1-2 times in the last year (54.5% of all respondents used the public health service). The respondents most often used gynecological (33%), ophthalmological (21%), and dermatological (15.5%). In turn, private medical care was used by 192 respondents (78%) out of all the respondents. Respondents revalued all assessed medical procedures by 27% for the diagnostic colonoscopy to 790% for a 20-minute massage at a rehabilitation clinic. Conclusion:  Cost awareness among polish students is poor. Lack of awareness of the costs of medical procedures (the amount that the public payer pays for specific procedures medical) that may have an impact on the use of healthcare services as well as health care expenses.